Psycho-social determinants in health state self-evaluation by Polish midwives - Iwanowicz-Palus, Grażyna J.; Bień, Agnieszka M.; Stadnicka, Grażyna; Golonka, Ewa (Polish Journal of Public Health, 2012)
Introduction. Professional work could be the source of life satisfaction, it could enhance the psychophysical condition. However it happens that professional activity brings negative effects and might be very aggravating.Aim. The work aimed at assessing psycho-social determinants in health self-evaluation by Polish midwives.Materials and method. The investigation was performed by means of the diagnostic polling method, using the questionnaire polls, and involved 3569 midwives from all regions of Poland. The method made use of the Polish adaptation of the Sense of Coherence Questionnaire SOC-29, a questionnaire poll for measuring sources of support, as well as a personal questionnaire to describe socio-demographic characteristics of the group.Results. Midwives who evaluated their mental health state as very good hardly ever or very rarely experienced difficult situations that triggered stress in their personal and professional lives (p=0.0000). In difficult situations, they always received support from their friends (p=0.001), their family (p=0.0024), their colleagues (p=0.0081), as well as from their superiors (p=0.0004). They also enjoyed a high global level of the sense of coherence (p=0.0000).Conclusions. Good self-evaluation of the investigated midwives was positively correlated with a high sense of coherence. There was also noted a correlation between very good and good self-evaluation of health state and support received from family, friends, colleagues and superiors.